Empowering Youth Posyandu Cadres to Enhance Reproductive Health Literacy in Purbatua PK Village - Fatimah Fatimah; Rahmah Juliani Siregar; Maryam Latifah Harahap (PT Inovasi Pratama Internasional, 2026)
Adolescent reproductive health remains a critical public health concern in rural Indonesia, where limited access to accurate information and cultural taboos often hinder open discussion on the topic. In Purbatua PK Village, the prevalence of early marriage and low reproductive health literacy among teenagers have been identified as major challenges. This community service program aimed to empower Posyandu (Integrated Health Post) youth cadres as community-based agents of change to improve reproductive health literacy among adolescents in the village. The program employed a participatory approach consisting of three main stages: (1) needs assessment through focus group discussions with cadres and community leaders, (2) intensive training sessions for 20 youth cadres covering reproductive anatomy, puberty, sexually transmitted infections, contraception, and the legal and psychosocial consequences of early marriage, and (3) ongoing mentoring and peer-education facilitation to enable cadres to disseminate information effectively to their peer groups. Evaluation was conducted using pre-test and post-test questionnaires to measure changes in knowledge, as well as observations of cadres' communication skills during peer sessions. Results showed a significant increase in cadres' knowledge scores, from an average of 58.5% in the pre-test to 89.3% in the post-test (p < 0.05). Furthermore, cadres demonstrated improved confidence and communication abilities in delivering sensitive reproductive health topics to their peers. Within three months of the program, peer-education sessions reached over 120 adolescents in the village. This empowerment initiative successfully strengthened local capacity for sustainable reproductive health education, contributing to the prevention of early marriage and the promotion of healthier reproductive behaviors among youth in Purbatua PK Village.